Leveraging the ARIS BI Toolkit to Equip Faculty for Career—and CAREER—Success - Jocelyn Bosley; Matthew Dwyer; Tisha Gilreath Mullen; Amanda Bohlin; Wern Ai Tan; Catherine M. Pelland; Ellen R. Iverson; Nathan Meier (The University of Alabama, 2024)
Research development professionals at the University of Nebraska-Lincoln (UNL) used the Center for Advancing Research Impact in Society (ARIS) Broader Impacts (BI) Toolkit with early-career faculty preparing grant proposals for the National Science Foundation's Faculty Early Career Development Program (CAREER). This prestigious career-development funding mechanism places unique emphasis on the integration of research and education, positioning awardees to enhance the impact of their research programs through education initiatives like curriculum development, outreach, and community engagement. However, many early-career faculty lack experience or training to develop robust education plans that are thoughtfully aligned with and responsive to their research. With the aim of developing practical ways to help faculty gain these skills, the study team used mixed methods to analyze the integration of research and education in CAREER proposals submitted by UNL faculty. These methods included using the ARIS BI Rubric to evaluate the proposals, convening two panel review discussions, and interviewing principal investigators about their ARIS BI Toolkit use and approach to research-education integration. Case study findings reveal that while effective and impactful integration can take many forms, early-career faculty and those who support them can utilize the ARIS BI Toolkit strategically to strengthen this aspect of grant proposals, positioning faculty to write well-integrated CAREER proposals and potentially contributing to long-term grant-writing and research program success.